#3**+2 **

Solve for x:

sqrt(x) + 2 = sqrt(x + 100)

Raise both sides to the power of 2:

(sqrt(x) + 2)^2 = x + 100

Subtract x + 100 from both sides:

-100 + (sqrt(x) + 2)^2 - x = 0

-100 + (sqrt(x) + 2)^2 - x = 4 sqrt(x) - 96:

4 sqrt(x) - 96 = 0

Add 96 to both sides:

4 sqrt(x) = 96

Divide both sides by 4:

sqrt(x) = 24

Raise both sides to the power of two:

** x = 576**

Guest Oct 16, 2019

#3**+2 **

Best Answer

Solve for x:

sqrt(x) + 2 = sqrt(x + 100)

Raise both sides to the power of 2:

(sqrt(x) + 2)^2 = x + 100

Subtract x + 100 from both sides:

-100 + (sqrt(x) + 2)^2 - x = 0

-100 + (sqrt(x) + 2)^2 - x = 4 sqrt(x) - 96:

4 sqrt(x) - 96 = 0

Add 96 to both sides:

4 sqrt(x) = 96

Divide both sides by 4:

sqrt(x) = 24

Raise both sides to the power of two:

** x = 576**

Guest Oct 16, 2019